Pelatihan Pembuatan Website Masjid As-Sholihin Baturaja Untuk Kemudahan Akses Informasi Jama’ah - Defi Pujianto; M.Romzi; Kadarsih Kadarsih (Lembaga Pengembangan Kinerja Dosen, 2025)
The As-Sholihin Baturaja Mosque is the center of religious activities and social activities for the congregation in the Ogan Komering Ulu district. However, there are limitations in conveying information, such as mosque activity schedules, information announcements, and other information. It is a challenge to provide optimal services, especially for mosque administrators. Therefore, training was carried out on creating a website to facilitate digital access to information and increase interaction between mosque administrators and congregation. The methods used include needs analysis, direct practice-based training on website operations, as well as evaluation of results through trial use of the website. This training involves participants from mosque administrators who are trained in managing websites using a simple and user-friendly platform. The results of the service are in the form of a website with the address https://masjid-ashsholihin.my.id. The results of this website show that this training was successful in improving participants' abilities in creating and managing websites independently. The resulting website is able to display important information such as prayer schedules, mosque activities and donations. With a website, congregation members find it easy to access information, thus increasing their involvement in mosque activities.